Justifiability of Littering: An Empirical Investigation - Benno Torgler; María A. García-Vali\~nas; Alison Macintyre (Center for Research in Economics, Management and the Arts (CREMA), 2008)
The paper investigates the relationship between environmental participation and littering. Previous empirical work in the area of littering is scarce as is evidence regarding the determinants of littering behavior. We address these deficiencies, demonstrating a strong empirical link between environmental participation and reduced public littering using European Values Survey (EVS) data for 30 Western and Eastern European countries. The results suggest that membership in environmental organizations strengthens commitment to anti-littering behaviour, thereby supporting improved environmental quality.
Keywords: H26; H73; D64; 330; littering; environmental participation; environmental preferences; environmental outcomes